The Long Road to Sámi Teacher Education - Elstad, Eyvind (Springer International Publishing, 2023)
Abstract Sápmi is the traditional term for the historical settlement area (the northern areas of Norway, Sweden, Finland and Russia) of the Indigenous people of this area, the Sámi. The school systems in Sápmi were imposed by Western educators and missionary workers in the eighteenth century. The road to a good Sámi school has had more than its fair share of obstacles, which is often a common experience at intersections between Indigenous peoples’ cultures and attempts by Western authorities to influence the mindsets and behaviour of Indigenous people. In the face of assimilation pressures, many Sámi lost their language and identity as a cultural minority. However, in the 1960s and 1970s, a new direction of Sámi education arose: the Norwegian, Swedish and Finnish education authorities decided that Sámi learners should have the opportunity to choose education in a Sámi language (of which there are several languages) in addition to receiving teaching in school subjects. Although the long road to Sámi teacher education has been a winding and tortuous path, today it is offered by two institutions (Sami University of applied sciences and Nord University). However, there are still challenges in obtaining enough teachers who have mastered Sámi languages.